Pengaruh Modifikasi Bermain Bola Bocce Terhadap Kemampuan Melempar Pada Siswa Tunagrahita Sedang - Puspitaningsari, Mecca; Satriyawan, Luky Nawil; Synthiawati, Novita Nur (Jurnal Porkes, 2022)
Adaptive Physical Learning is an integral part of an overall education that aims to develop aspects of physical fitness, movement skills, critical thinking skills, social, reasoning, emotional, mental retardation is a term used to describe children who have intellectual abilities below the average. This study aims to test the modification of playing bocce ball on the throwing ability of moderately mentally retarded students at SLB Paedagogia Maospati for the 2020/2021 academic year. The subjects of this study were students with moderate mental retardation in grade VIII at SLB Paedagogia Maospati for the 2020/2021 academic year. The sample in this study amounted to 1 person because it used Single Subject Research (SSR).The design used in this study is A1 – B – A2. With 8 meetings for thephase baseline A1, Intervention andphase baseline A2. In playing throwing activities, the results of the baseline A1 25 and A2 87 baseline values obtained from the mean level data. The results of this study indicate that the modified effect of playing bocce ball on throwing ability has increased in number from the baseline phase to the intervention phase which indicates a decrease in sedentary behavior from the baseline stage (A1) to the intervention stage (B) decreased in number by (-25%) and there was 0% overlapping of data. And there was an increase in the number of steps from the intervention stage (B) to the baseline stage (A2) by (+8%) and there was 0% overlapping of data.